2022
DOI: 10.3390/medicina58030377
|View full text |Cite
|
Sign up to set email alerts
|

Predictive MRI Biomarkers in MS—A Critical Review

Abstract: Background and Objectives: In this critical review, we explore the potential use of MRI measurements as prognostic biomarkers in multiple sclerosis (MS) patients, for both conventional measurements and more novel techniques such as magnetization transfer, diffusion tensor, and proton spectroscopy MRI. Materials and Methods: All authors individually and comprehensively reviewed each of the aspects listed below in PubMed, Medline, and Google Scholar. Results: There are numerous MRI metrics that have been proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 199 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…Among these parameters, white matter lesions (WMLs) are a characteristic feature of MS, which are usually detected by contrast-enhanced MRI. Recent research has revealed that GM abnormalities manifest early in the course of the disease and predict both conversion to MS and the progressive accrual of disability [ 86 ]. Moreover, GM atrophy is more severe than WM atrophy in the early stages of the disease [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these parameters, white matter lesions (WMLs) are a characteristic feature of MS, which are usually detected by contrast-enhanced MRI. Recent research has revealed that GM abnormalities manifest early in the course of the disease and predict both conversion to MS and the progressive accrual of disability [ 86 ]. Moreover, GM atrophy is more severe than WM atrophy in the early stages of the disease [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-linear progression of this scale, the non-uniform progression between different stages, and the inter and intra-assessor variability when implementing at different clinical visits. It is also not easy to implement and imprecise at the lower end of the scale, too driven by mobility distances at the middle and higher end of the scale and fails to take into account upper limb function which means a patient can score very highly for having one severe cord relapse ending the patient wheelchair dependent [24][25][26].…”
Section: No Evidence Of Disease Activity (Neda)mentioning
confidence: 99%
“…In these days, the successive increase in neurodegenerative features is clinically estimated by indirect measurements of relevant parameters, such as disability accumulation (expanded disability status scale—EDSS), cognitive tests, and brain atrophy index based on magnetic resonance imaging (MRI) [ 12 ]. Nevertheless, reliable biomarkers indicating an accurate estimation of quality and degree of neurodegeneration during MS progression are still missing [ 13 , 14 ].…”
Section: Multiple Sclerosismentioning
confidence: 99%